Technique to Choose Best Portfolio on The Basis of Companies’ Performance - Javaid Iqbal Faqir Muhammad, Fazal Husain (JSSH, 2023)
The construction of portfolios on the basis of CAPM beta becomes difficult if Capital Asset Pricing Model (CAPM) fails to explain returns. A test of CAPM on Karachi Stocks Exchange (KSE) shows a negative linear relationship between stocks beta and its returns for the period July 2007 to June 2013 and no relationship for July 2010 to June 2013.